PENGARUH SISTEM INFORMASI MANAJEMEN ENTERPRISE RESOURCE PLANNING (ERP) DAN KOMPETENSI KARYAWAN TERHADAP PRODUKTIVITAS KERJA (SURVEY PADA PT INDORAMA SE-JAWA BARAT) - Mia Maela Fatimah; Yofy Syarkani (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2020)
This study aimed to examine the influence of ERP management information system and employe’s competency on performance productivity at PT. Indorama in West Java. The model is based on research problem, that there is deviation between production target and realization. It is assumed that deviation occur because ERP information system and competency are not implement properly so there is gap on production target. Production target supporting by ERP information system and competency. The method that use in this research is quantitative descriptive method. Analysis unit in this research is oracle users which total 434 users such as population and got sampel 100 users by using Maksimum Likelihood (ML) techniques. Collecting data techniques in this research is study documentation, interview and quetioner. The analysis technique used to test the influence among variables is PLS SEM analysis. The study resulted that is a positive aspect from the influence of ERP management information system and employe’s competency on performance productivity at PT. Indorama in West Java.